Microplastic Presence in the Digestive Tract of Pearly Razorfish Xyrichtys novacula Causes Oxidative Stress in Liver Tissue - Amanda Cohen-Sánchez; Antònia Solomando; Samuel Pinya; Silvia Tejada; José María Valencia; Antonio Box; Antoni Sureda (Toxics, 2023)
Plastic pollution in the oceans is a growing problem, with negative effects on exposed species and ecosystems. Xyrichtys novacula L. is a very important fish species both culturally and economically in the Balearic Islands. The aim of the present study was to detect and categorise the presence of microplastics (MPs) in the digestive tract of X. novacula, as well as the existence of oxidative stress in the liver. For this purpose, the fish were categorised into two groups based on the number of MPs observed in the digestive tracts: a group with no or low presence of MPs (0–3 items) and a group with a higher presence of MPs (4–28 items). MPs were found in 89% of the specimens analysed, with a dominance of fibre type and blue colour. Regarding the type of polymer, polycarbonate was the most abundant, followed by polypropylene and polyethylene. For the group with a greater presence of MPs, the activities of the antioxidant enzymes glutathione peroxidase and glutathione reductase, as well as the phase II detoxification enzyme glutathione s-transferase, were higher than the activities observed in fish with little to no presence of MPs. The activities of catalase and superoxide dismutase and the levels of malondialdehyde did not show significant differences between both groups. In conclusion, these results demonstrate the presence of MPs in the digestive tract of X. novacula and the existence of an antioxidant and detoxification response, mainly based on the glutathione-based enzymes.